Influence of Crumb Rubber and Recycled Steel Fibers on Hybrid Layered Reinforced Concrete Columns under Compression Load - Alasmari, Hasan (Engineering, Technology & Applied Science Research, 2024)
Waste tires pose an environmental issue that causes health problems when discarded by either land burial or burning. The current study investigated the properties and characteristics of different-length hybrid layered columns of Recycled Steel Fibers (RSF) at a fixed ratio (0.6%) of the volume fraction with utilized fixed content (15%) of Crumb Rubber (CR). Nine square column specimens were prepared and tested under axial compression load to reveal the effect of RSF and CR content on hybrid layered reinforcement columns. The results revealed that as the RSF content increased concrete’s properties were enhanced. However, the inclusion of CR at the top layer resulted in performance reduction. Additionally, the layered structure with CR and RSF has higher characteristic properties, including higher load capacity and displacement. Moreover, adding 0.6% RSF to both layers and CR at the top led to a 120% increase in the toughness of the concrete loading capacity. This was followed by a reasonable improvement in displacement and ductility.